Penggunaan Media Animasi Audio Visual untuk Meningkatkan Hasil Belajar IPA di SD Negeri 2 Kota Ternate - Taslim Buaja; Rahayu Ramadanaryanthi; Safri Miradj (CV. Creative Tugu Pena, 2024)
The Study done with objective For know the use of audio visual animation media in science subjects in improving learning outcomes of class VI A students of SD Negeri 2 Kota Ternate. The type of research used is Classroom Action Research (CAR). The subjects in this study were 30 class VI A students consisting of 17 boys and 13 girls. The implementation of the action was carried out in 2 cycles and each cycle was carried out in 2 meetings. Each meeting must go through 4 stages, namely planning, implementation, observation, and reflection. After the implementation of cycle I, the students' learning outcomes with an average value of 67 or classical completeness were 16 students (53%). Furthermore, in cycle II, an average value of 77 was obtained with classical completeness of 27 students (90%). Based on the results of the study, it can be concluded that audio-visual animation media can improve science learning outcomes, especially in the material of simple electrical components in class VI-A students of SD Negeri 2 Kota Ternate